Digging machines - Earl, Amanda (Wayland Hove, 1994)
Why is a spoon a good tool for picking up flour? What does the inside of a road breaker look like? How much earth can a backhoe excavator move at one time? This book will help you understand how the digging tools and machines you may use or see around you work. Find out about the enormous digging machines used in industry, such as bucket wheel excavators, dredgers, and tunnel boring machines. Table of contents: * Spooning for food * Digging in sand * Digging in soil * Ploughing fields * Road breaking * Building foundations * Excavating * Clearing ground * Clearing snow * Digging under water * Mining * Digging a tunnel